Waste to Energy Financial Model Design Based on Resident Participation - Nadya Amalin, Farizal; Rachman, Amar (European Journal of Sustainable Development, 2019)
This study designed a financial model for utilizing municipal solid waste (MSW) to generate energy based on resident participation. This effort is crucial since in many cases a government has some competing programs to be funded on its limited money. This makes a public project does not receipt enough funding to run the best option available or even the project sometime has not funded at all. On the other side, regulation and social responsibility factors inhibit private sector to invest their money on it. Based on willingness to pay research conducted at the City of Depok, it was shown that the residents are willing to spend their money to get a better MSW treatment through funding a Sustainable Modular Landfill Gas Plant project. A financial model developed for the project showed that the project is feasible. The project gave a positive net present value and internal rate of return greater than the average Indonesian bank interest rate; that is 13.87% for no electricity discounts scenario and 13.73% for electricity discount scenario. Further analysis showed that the minimum number of resident to participate on the project are 7% and 51% of the total Depok household, respectively. Keywords: Financial model, waste to energy, landfill gas plant project, net present value, internal rate of return.